A spaceborne, pulsed UV laser system for re-entering or nudging LEO debris, and re-orbiting GEO debris. (January 2016) - Phipps, Claude R.; Bonnal, Christophe
Abstract: Among the problems raised by the presence of debris in Earth Orbit, the question of large derelict satellites in Geostationary Orbit (GEO) is of major importance. More than 1000 defunct GEO satellites cruise in the vicinity of this unique orbit and pose the question of orbital slot availability. It is proposed to use lasers in GEO to reorbit the large debris in the graveyard zone, some 300 km above GEO. The principle of orbital transfer by laser ablation is recalled, and two different methods are described. These lasers can also serve for small debris deorbiting and large debris nudging in Low Earth Orbit (LEO). Technical details are provided, as well as a preliminary mass budget. Highlights: First effective method for raising the orbits of uncontrolled, multi-ton GEO satellites in a few hours to make room for new equipment. Installed in LEO, can nudge multi-ton objects to avoid predicted collisions. Can also cause small LEO debris <50 g to re-enter and harmlessly burn up. Solar-powered UV laser system with 8–10 kW average optical power. Estimated system costs of order 200 M installed.